Social contexts of fertility desire among non-childbearing young men and women aged 15-24 years in Nigeria - Joshua O. Akinyemi; Clifford O. Odimegwu (BMC, 2021)
Plain Language Summary Reduction in ideal number of children has been suggested as a necessary condition for fertility decline especially in high fertility countries of Western and Central Africa. In this study, we explored the effects of individual, household as well as community characteristics on fertility desires among young men and women aged 15-24 years in Nigeria. We analysed data for 2674 males and 9637 females aged 15-24 years extracted from the 2018 Nigeria Demographic and Health Survey. The outcome variable was desire for large family size (DLFS) defined as ideal number of children greater than four. Results showed that DLFS was 71% among men and 53% in women. Individual-level factors associated with DLFS among men include Islam religion, household size and wealth status. Geo-political region and high level of negative attitude to family planning were the main community-level factors associated with DLFS. For women, individual-level positively associated with DLFS were Islam religion, and being currently married. Compared to Yoruba, other ethnic groups were more likely to favour DLFS. The negative factors associated with DLFS among young women include higher education and wealth status. At the community-level, Northern geo-political regions, child mortality experience and negative attitude to family planning were positively associated with DLFS. The influence of religion, household wealth and attitude to family planning differ between young men and women. Multi-dimensional strategies with active communication and programmatic interventions are needed so that desire for large family size by young men and women do not slow down fertility transition in Nigeria.